Herpesvirus and neurological manifestations in patients with severe coronavirus disease - Carneiro, Vanessa Cristine de (2022)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Virologia Molecular. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Desenvolvimento Tecnológico em Virologia. Rio de Janeiro, RJ, Brasil.